1983
DOI: 10.1093/geronj/38.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Parathyroid Hormone and 25 Hydroxycholecalciferol Levels

Abstract: Serum parathyroid hormone and 25 hydroxyvitamin D were measured in 124 normal subjects aged from 20 to 90 years. There was a significant progressive increase in serum parathyroid levels with age associated with a progressive decrease in total serum calcium. After the sixth decade there was a significant reduction of 25 hydroxyvitamin D serum levels. In each age group, there were no significant differences between men and women in all parameters measured. In normal elderly subjects there is an age-related decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 0 publications
6
39
3
2
Order By: Relevance
“…Further, the lack of correlation between age and mid-molecule PTH in the present study suggests that there was no age-related change in renal clearance of PTH fragments in these subjects. Chapuy et al 26 suggested that age-related decreases in intestinal absorption of calcium results in increased secretion of PTH and that the decreased absorption is due to reduced synthesis of 1,25-dihydroxyvitamin D in older people as reported by Gallagher et al 27 We could not confirm this hypothesis with our results since we observed no decrease of serum calcium with age.…”
Section: Scontrasting
confidence: 75%
“…Further, the lack of correlation between age and mid-molecule PTH in the present study suggests that there was no age-related change in renal clearance of PTH fragments in these subjects. Chapuy et al 26 suggested that age-related decreases in intestinal absorption of calcium results in increased secretion of PTH and that the decreased absorption is due to reduced synthesis of 1,25-dihydroxyvitamin D in older people as reported by Gallagher et al 27 We could not confirm this hypothesis with our results since we observed no decrease of serum calcium with age.…”
Section: Scontrasting
confidence: 75%
“…The expression of osteocalcin is stimulated by 1 ,25-dihydroxyvitamin D3 [1,25-(OH )2D3] and further modulated by other local factors such as TGF-# (38)(39)(40)(41). While some studies report decreased circulating levels of 1,25(OH)2D3 with age (42)(43)(44), similar findings were not observed by others (45)(46)(47). Nevertheless, an impaired ability ofthe aging kidneys to convert 25-hydroxyvitamin D3 to 1,25-(OH)2 D3 may contribute to lower circulating levels with age (44,46,48).…”
Section: Discussionmentioning
confidence: 53%
“…The differences in both parameters over the age range were equivalent to reductions of −0.41% and −0.65%, respectively, consistent with a continuing loss of skeletal integrity throughout life at the cortical and trabecular level. It has been postulated that enhanced PTH secretion, secondary to compromised vitamin D status or metabolism, may induce or exacerbate bone loss in older individuals [27][28][29]. Moreover, interventional data have confirmed the role of vitamin D deficiency in the pathogenesis of agerelated osteoporosis and indicated the need to maintain serum cholecalciferol levels within the normal range in elderly people [30].…”
Section: Discussionmentioning
confidence: 99%